2021
DOI: 10.1186/s12906-021-03435-7
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of combining curcumin, bromelain and harpagophytum to reduce inflammation in osteoarthritic synovial cells

Abstract: Background Osteoarthritis (OA) is the most common form of arthritis, affecting millions of people worldwide and characterised by joint pain and inflammation. It is a complex disease involving inflammatory factors and affecting the whole joint, including the synovial membrane. Since drug combination is widely used to treat chronic inflammatory diseases, a similar strategy of designing plant-derived natural products to reduce inflammation in OA joints may be of interest. In this study, we charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…It also decreased IL-6 release and the production of PGE2. This indicates that the combination of these three compounds may reduce inflammation and pain (24).…”
Section: Discussionmentioning
confidence: 89%
“…It also decreased IL-6 release and the production of PGE2. This indicates that the combination of these three compounds may reduce inflammation and pain (24).…”
Section: Discussionmentioning
confidence: 89%
“…This conclusion has been verified in many experiments. Taking CUR as an example, CUR alleviates inflammatory diseases by reducing major markers of inflammation, such as IL-6 and TNF-α, malondialdehyde, sensitive C-reactive protein, MCP-1 ( 114 116 ). The anti-inflammatory effect of dietary polyphenols is the basis of their biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory actions of bromelain from the context of osteoarthritis were explained by a 2021 study, in which the enzyme extract is shown to suppress glycosaminoglycan (GAG) and hence counteract the degradative effects of IL-1β and MMPs [335]. Brochard et al (2021) demonstrated that bromelain has a similar effect on lipopolysaccharideinduced inflammation, albeit in a combinatorial form with curcumin and Boswellia serrata [336]. Similar effects were observed by Quarta and colleagues (2022) in an in vitro model of inflammation [337].…”
Section: Bromelainmentioning
confidence: 99%